The Hierarchical Pyramid Pentuple P Bottom Line as the Implementation of Corporate Social Responsibility - Badria, Nuril; Hasanah, Naimatul (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the measurement of the achievement of business sustainability of PT. Bank Negara Indonesia Tbk through the pyramid of the bottom line pentuple p hierarchy. The pentuple p bottom line is a reconstruction of the triple bottom line that encourages the implementation of a company's business sustainability, the triple bottom line consists of profit, people and planet into a pentuple bottom line consisting of people, profit, phenotechnology, planet, and Prophet (5P). This study is a non-positivist research that uses a postmodernist paradigm with an imaginary dialogue research method consisting of two professions, namely accountants and investors at PT Bank Negara Indonesia. The results of this study are the pyramid of the bottom line pentuple hierarchy as a measurement of the success of fulfilling social responsibility at PT. Bank Negara Indonesia Tbk. Hierarchical pyramid is a model of corporate obligations starting from people to prophets which are explained at each level. First, people are BNI's efforts to provide benefits and benefits to stakeholders and not exploit or harm a group of people. Second profit is an effort to achieve organizational performance, third Phenotechnology is the fact that the existence or phenomenon of information technology must be an important part in maintaining the survival of an organization. The fourth planet is environmental sustainability, nature must be fought for by BNI, and the last Prophet is the balance of spirituality, mentality, or spirituality in the process of preserving life.